INCREASING THE STUDENTS READING COMPREHENSION OF REPORT TEXT WITH SOCRATIVE APPLICATION - Sahrir, Vinky Audrini; Hamid, Radiah; Azis, Awaliah (English Language Teaching Methodology, 2023)
This research aims to find out the increasing of students reading comprehension of report text by using Socrative Application, especially on literal comprehension and interpretive comprehension in 10th grade students of SMA Negeri 14 Makassar.The research applied Pre-Experimental Method using one group pre-test and post-test research and collect data through pre-test and post-test instruments. The sample in this study was  X MIPA 4 SMA Negeri 14 Makassar which amounted to 36 students. Samples was taken by using the Purposive Sampling Technique. The data obtained was also analyzed using SPSS Application version 25. Based on the research findings, before utilizing the advantages of the Socrative Application, namely ease of use, educational benefits or instant feedback, and quiz format and assessment of student mean score on literal comprehension is 49.4 and interpretive comprehension is 41.6. After utilizing the advantages of the Socrative Application the average student on literal comprehension becomes 70, while for interpretive comprehension is 51.2. The occurrence of this significant increase in literal comprehension is due to the advantages of the Socrative Application which can increase students' literal comprehension while the absence of significant increase in students' interpretive comprehension occurs due to the difficulty of students inrking conclusions on the Socrative Application.Therefore, based on these results, it is recommended to use Socrative Application at reading comprehension, especially in literal comprehension.